Development of an Improve Power Factor Corrector Trainer Set - Asan, Muhammad Izzuddin; Binti Norjali, Rasida; Mohamad Syah Rizal Abdullah (Progress in Engineering Application and Technology, 2024)
The main goal of this study is to find out how common power factor correction (PFC) method works. Using the APFC trainer, the experiment looks at different types of loads, such as resistive, inductive, and capacitive loads with different value. After that, the test results are compared to theoretical calculations to see how good the trainer is at adjusting power factor correctly. The study tries to find out if changing the value on the capacitive load can help get the desired power factor under different load conditions. The research results help to understand how APFC (Automatic Power Factor Correction) systems can be used in real life to improve the efficiency of power factors in electrical systems. The study shows that the APFC trainer can change the power factor for different loads, which is very close to what theoretical calculations predicted would happen. By changing the APFC trainer's and RLC load parameters in a planned way, the desired power factor is always reached in the experimental setup. The results show that APFC systems can work in real life, which is useful information for understanding how they can make electrical networks more efficient and improve the quality of power. This study shows how important it is to use APFC technology to improve power factor management.